Analysis of project about Cerrado fruits developed with students from two public schools - Rodrigues, D. B.; Costa, L. T.; Melo, C. P. O. F.; Souza, A. G.; Garcia, E. M.; Taroco, H. A.; Melo, J. O. F. (Scientific Electronic Archives, 2016)
The Brazilian Cerrado has enormous diversity featuring a large number of fruit native plants that have a high nutritional value and distinctive flavor. This work belongs to an extension program of Cerrado fruits, where two species stand out in this region: Cagaita tree (Eugenia dysenterica DC) and Pequi tree (Caryocar brasiliense). The same was done in a neighborhood located near the Federal University of Sao Joao del Rei, Campus of Sete Lagoas - MG and developed in two municipal schools, with the participation of students of 4th and 5th years and other servers. The goal of this project was to disseminate knowledge to the participants of the reality that surrounds them, and on these two fruits of the Cerrado, providing support materials for environmental preservation awareness. The work took four steps, one of which was to answer a questionnaire by students. The main results showed that students, teachers and cooks did not know Pequi and Cagaita, native fruit species of one of the richest biomes and threatened the world. It was possible to realize the interest of those involved in the project, in order to educate about the importance of ensuring the collection and use of these fruits for the next generations.